Localização de proteínas superficiais de Leptospira interrogans por imunofluorescência - Timm, G. N. R.; Souza, J. D.; Grassmann, A. A.; Mcbride, A. J. A. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Leptospirosis is a neglected zoonosis with a worldwide distribution caused by pathogenic spirochetes belonging to the Leptospira genus. Vaccines are the most efficient prophylactic measure for infectious diseases. However, the current vaccine against leptospirosis has numerous disadvantages, such as short-term protection and serovar-related specificity, and, in Brazil, it is only available for animals. Thus, there is a need to develop a new vaccine that can overcome these problems and that can be used in humans. Hence, the discovery of new proteins that are exposed on the bacterial surface, which are promising antigens for a new vaccine, could overcome the shortcomings of bacterin vaccines.